Analisis Exegesis Kata ἐΠΙΕΙΚὲΣ dan Implikasinya terhadap Terjemahan dari Filipi 4:5 - Subriyanto Subriyanto; Jemmy C. Najoan (Departement of Mathematics Education, 2023)
The translation of the word ἐπιεικὲς in Philippians 4:5 is inviting trouble as the Indonesian translation does not seem to be very appropriate based on the context. While many versions of the Bible give the correct translation, the discussion about why the translation was given has never appeared. This article discusses the use of the word ἐπιεικὲς in the verse in question based on three points of view. First, it analyzes the usage of the word in the New Testament. Secondly, it analyzes the near context of the verse under study. Third, the analysis of the sequential order that usually appears in Paul's writings. Fourth, the analysis of the broader context. The four analyses prove that when Paul uses the word ἐπιεικὲς he is referring to the context of suffering, which is why the correct meaning for the translation of the word ἐπιεικὲς is forbearance. Thus, Jesus' teaching on almsgiving in Matthew does not contradict Philippians 4:5.